Wear hot-gas plasma coatings under fretting-corrosion - Краля, В.О.; Хімко, А.М.; Якобчук, О.Є. (Proceedings of National Aviation University (archive), 2006)
It is analyzed fretting ability of plasma gas-thermal covers: ВКНА, ПГ10Н-01, ПС12НВК-01 and molybdenum. Researches are carried out in a broad band of amplitudes and loadings. It is revealed, that with the magnitude variation of movement intensity of wear of covers varies. There is a fixed area where there is a changeover of processes with friction surfaces, from mechanical-chemical on fatigue-abrasive which changes character of wear with linear on parabolic. Its numerical value depends on requirements of loading. Researches will allow selecting and applying covers to recovery of clusters of abrasion adequately.